High-throughput sequencing of T-cell receptor alpha chain clonal rearrangements at the DNA level in lymphoid malignancies - Komkov, Alexander; Miroshnichenkova, Anna; Nugmanov, Gaiaz; Popov, Alexander; Pogorelyy, Mikhail; Zapletalova, Eva; Jelinkova, Hana; Pospisilova, Sarka; Lebedev, Yuri; Chudakov, Dmitriy; Olshanskaya, Yulia; Plevova, Karla; et al. (British journal of haematology, 2020)
Rearrangements of T- and B-cell receptor (TCR and BCR) genes are useful markers for clonality assessment as well as for minimal residual disease (MRD) monitoring during the treatment of haematological malignancies. Currently, rearrangements of three out of four TCR and all BCR loci are used for this purpose. The fourth TCR gene, TRA, has not been used so far due to the lack of a method for its rearrangement detection in genomic DNA. Here we propose the first high-throughput sequencing based method for the identification of clonal TRA gene rearrangements at the DNA level. The method is based on target amplification of the rearranged TRA locus using an advanced multiplex polymerase chain reaction system and high-throughput sequencing, and has been tested on DNA samples from peripheral blood of healthy donors. Combinations of all functional V- and J-segments were detected, indicating the high sensitivity of the method. Additionally, we identified clonal TRA rearrangements in 57 out of 112 tested DNA samples of patients with various T-lineage lymphoproliferative disorders. The method fills the existing gap in utilizing the TRA gene for a wide range of studies, including clonality assessment, MRD monitoring and clonal evolution analysis in different lymphoid malignancies.
Keywords: acute lymphoblastic leukaemia; DNA nádorová; Female; DNA, Neoplasm; ženské pohlaví; High-Throughput Nucleotide Sequencing; Lymphoproliferative Disorders; lidé; genová přestavba - alfa řetězec receptoru antigenů T-buněk; clonal rearrangements; multiplexová polymerázová řetězová reakce; Humans; Multiplex Polymerase Chain Reaction; Male; hematologické nádory; Hematologic Neoplasms; vysoce účinné nukleotidové sekvenování; lymfoproliferativní nemoci; T-cell receptor alpha chain; high-throughput sequencing; mužské pohlaví; lymphoproliferative disorders; Gene Rearrangement, alpha-Chain T-Cell Antigen Receptor